Publikasi Konten Politik pada Masa Tenang Kampanye Pemilu: Tindak Pidana Pemilu atau Kebebasan Berekspresi? - Nawa, Fridolin (UNES Law Review, 2024)
The legal framework Election in Indonesia regulates the methods and campaign periods allowed for electoral participants. The election campaigns are supposed to end at the start of election campaign’s quiet period. However, due to the evolution of campaign methods, particularly through the internet, there are still instances where advertisements and social media content related to electoral participants, whether by the participants themselves or others, continue to be circulated. Therefore, standards for conducting election campaigns must be fairly regulated. This article discusses the intersection between freedom of expression and elction crime during the quiet period, examining the stipulations of the Indonesia Election Law. Research reveals that the current regulations are ambiguous, leading to ongoing debates in election law enforcement. Campaign activities during the quiet period contradict electoral laws and may result in penalties ranging from administrative to criminal sanctions.